EARTHEN ARCHITECTURE AND SOCIOCULTURAL CHALLENGES - Guillaud, Hubert; Houben, Hugo (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The direct link between earthen architectural heritage conservation and local sustainable development has been recently established but it sounds necessary to enlarge the criteria and the spectrum of values to be considered in order to adapt to current global challenges and facilitate efficient implementations at different scales. It is of major importance to integrate the analysis of political, economical, environmental, human, social, scientific, technical and educational values. This paper intends to present a contribution to the definition of a new cultural foundation between heritage, contemporary construction-related practices and sustainable development, offering a different approach of the notion of cultural significance and demonstrating its importance for the future. "Anything that degrades culture shortens the path that leads to servitude" (Char, 1951).